EFFECT OF TRIGONAL STRESS ON THE OPTICAL ABSORPTION SPECTRA OF GaP:Ti3+ - Jamila, S.; Naqvi, S.M.M.R. (Journal of Research (Science), 2004)
Applying the theory developed for strongly coupled ions, the GaP:Ti3+ Jahn-Teller system has been modeled under a trigonal uniaxial stress in the [111] direction, since previous models have been found to be inappropriate. In this model second order stress terms have been incorporated and the results obtained are compared to the earlier linear model.